Alexander Dallas Bache Building the American Nation through Science and Education in the Nineteenth Century - Jansen, Axel (Campus Verlag, 2011)
Alexander Dallas Bache was the key leader of antebellum American scientists. Presuming his profession to be a herald of an integrated U.S. nation-state, Bache guided organizations such as the United States Coast Survey, then the country's largest scientific enterprise. In this analytical biography, Axel Jansen explains Bache's efforts to build and shape public institutions as a national foundation for a universalistic culture-efforts that culminated during the Civil War when Bache helped found the National Academy of Sciences as a symbol for the continued viability of an American nation. https://creativecommons.org/licenses/by-nc-nd/4.0/